2022
DOI: 10.1136/bmjopen-2021-060387
|View full text |Cite
|
Sign up to set email alerts
|

Health system readiness for non-communicable diseases at the primary care level: a systematic review

Abstract: ObjectiveTo synthesise evidence on the primary healthcare system’s readiness for preventing and managing non-communicable diseases (NCDs).DesignSystematic review.Data sourcesOvid MEDLINE, EMBASE, CINAHL, PsycINFO and Scopus were searched from 1 January 1984 to 30 July 2021, with hand-searching references and expert advice.Eligibility criteriaAny English-language health research with evidence of readiness/preparedness of the health system at the primary healthcare level in the context of four major NCDs: diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…On the other hand, clinical practice guidelines and continues training are very important to improve both the quality or process of care and patient outcomes (16) An interesting finding in our study is that only 25% of participants received training about chronic diseases benefit package during the last three years while around 50% of the facilities lack effective national protocols or guidelines for treating chronic diseases. These finding come in line with study conducted in Sir-lanka where primary health care providers reflect the insufficient knowledge and training about preventive measure to control and improve the quality of chronic diseases management (15) , and cross-sectional study healed in Cape Town for NCDs at 30 PHC facilities. 14 health professionals were interviewed and they revealed shortage in time and indicated the importance of workshops and group meeting in patient education and empowerment beside that the study revealed significant gab in presence of these guidelines, also a qualitative study done in Palestinian showed that health providers did not used updated clinical guidelines, but this study was done in done in public hospitals not at PHC context.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, clinical practice guidelines and continues training are very important to improve both the quality or process of care and patient outcomes (16) An interesting finding in our study is that only 25% of participants received training about chronic diseases benefit package during the last three years while around 50% of the facilities lack effective national protocols or guidelines for treating chronic diseases. These finding come in line with study conducted in Sir-lanka where primary health care providers reflect the insufficient knowledge and training about preventive measure to control and improve the quality of chronic diseases management (15) , and cross-sectional study healed in Cape Town for NCDs at 30 PHC facilities. 14 health professionals were interviewed and they revealed shortage in time and indicated the importance of workshops and group meeting in patient education and empowerment beside that the study revealed significant gab in presence of these guidelines, also a qualitative study done in Palestinian showed that health providers did not used updated clinical guidelines, but this study was done in done in public hospitals not at PHC context.…”
Section: Discussionsupporting
confidence: 84%
“…These findings come in line with a systemic review that include 23 studies which assess the readiness of health system for providing integrated package for chronic diseases. The result of the review demonstrated that almost all countries' healthcare systems have suffered from inadequate supply side responses to medicine, technologies, equipment, trained healthcare professionals, health information and leadership and stewardship (15) .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PHC levels across the south Asian and sub-Saharan countries have insufficient supplies of medicines, basic amenities, diagnostic facilities, and workforce ( 50 ). In line with our review paper, the findings of this study revealed that insufficient resource mobilization is affecting NCD service delivery that needs to be emphasized to make the health system more responsive ( 48 ). Functional referral services and record-keeping are the integral components of a strong health system that ensures patients have access to the best possible higher-level facilities, utilize resources, and maintain the standardized process in service provision ( 51 ).…”
Section: Discussionsupporting
confidence: 83%
“…The constant shortage of medicines, diagnostic facilities, equipment, and trained human resource remains a big challenge in NCD service delivery, which is a common feature of the PHC system in many LMICs, including Bangladesh ( 20 , 48 , 49 ). It was reported that PHC levels across the south Asian and sub-Saharan countries have insufficient supplies of medicines, basic amenities, diagnostic facilities, and workforce ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of noncommunicable disorders such as hypertension, heart diseases, type 2 diabetes mellitus, obesity, cancer, and mental health disorders continues to grow globally despite continued research and developments in biomedicine. [ 2 ] Considering the emerging scientific evidence and increasing demand from the patient population, the mainstream health systems world over are opening up for the process of integration with the traditional systems of medicine. Various committees were set up by the government to plan and implement integrative medicine from the 1940s onwards (Bhore committee, Chopra Committee, and Udupa Commitee).…”
Section: Need For Integration Of Medicinementioning
confidence: 99%